(untitled) (MAUSAM, 1966)
Research in the last decade has shown that one of the meteorological parameters which is associated with clear air turbulence (CAT) is Richardson’s Number. To make Richardson number Ri useful for forecasting the location and intensity of CAT, we made a study under Indian conditions of the association between CAT and different ranges in the values of Ri. In this paper a set of nomograms is presented by which Ri may be estimated without elaborate calculations and with a fair degree of accuracy for the layer between 300 and 200 mb. Similar nomograms can be prepared for other isobaric levels for the use of different types of aircraft in operation in India. If a singularity, like a wind maximum, is found between 300 and 200 mb, Ri may be also computed separately for the layer between 300 mb and the level of maximum wind and for the layer between the level of maximum wind and 200 mb.